Women, Sheep, and Textiles: The social significance of ram’s head beads in Early Iron Age Slovenia - C. Frie, Adrienne (Arheološki vestnik, 2021)
Ram’s head beads are well-known items of personal adornment in the Dolenjska Hallstatt cultural group. Recent analysis has demonstrated that they are the most common zoomorphic artefacts in this region with 187 currently known. This article updates the list of known beads and contextualizes their significance in the Dolenjska Hallstatt cultural group. It is argued that the sheep imagery of these beads and their distribution in female graves is related to local textile production. It is proposed that beads signalled aspects of personal and economic identity for Dolenjska Hallstatt women related to the production of high-quality textiles. In addition, the distribution of these beads demonstrates Iron Age community networks on the western frontier of Dolenjska, and perhaps even reflects the movement of women between communities.